Produção de celulases por fermentação em estado sólido a partir de Melanoporia sp. e Mucor circinelloides utilizando bagaço de cana-de-açúcar como substrato - Maciel, Tatiane Cavalcante (2013)
Sugarcane bagasse is a lignocellulosic residue obtained from sugarcane mechanical pressing for juice extraction. This biomass is abundant in Brazil because the country is the world’s largest manufacturer of sugar and ethanol. The use of sugarcane waste as substrate for enzymes production, such as cellulases, is an interesting and viable option since the production costs of these enzymes are high, which limits its industrial use. In this context, potential cellulase-producing strains have been extensively studied in order to develop less costly cellulolytic enzymes complexes. In this study, the production of cellulases by Mucor circinelloides. and Melanoporia sp through solid state fermentation of sugarcane bagasse and the effects of selected parameters for enzyme production were evaluated. The investigated physicochemical parameters associated with the growth of the microorganisms and enzyme production were: initial pH of the growth medium, temperature and time of enzyme production. Regarding nutritional parameters, the effect of Tween 80 and different sources of mineral salts and organic nitrogen and were studied. In addition, tests were performed in order to define the best combination of pH and temperature for the determination of enzyme activity. For M. circinelloides, the maximal enzyme activity (15.87 FPU / g) was achieved with a fermentation medium composed of 3g of sugarcane bagasse, 2mL of saline solution containing 0.1 g/L of CuSO4, 9.0 g/L of (NH4)2SO4 e 1.0 g/ L of KH2PO4 and 0.8% Tween 80 (v/v) at pH 5.48 incubated at 34.4 °C for 48 hours. The optimum combination of pH and temperature was at pH 6.5 and 60 °C. For Melanoporia sp. the higher enzymatic activity obtained was 14.21 FPU / g as a result of using 3g of sugarcane bagasse with the addition of 2mL of saline solution containing 9.0 g/L of (NH4)2SO4, 1.0 g/ L of KH2PO4 and 0.2% Tween 80 (v/v) at pH 6.28 and incubated at 30°C for 48 hours. The optimized conditions of pH and temperature for enzymatic activity determination were pH 7.0 and 60°C. The results demonstrated the high potential of the two strains under investigation, which presented the higher enzyme activity at pH in the neutral range. This result represents a technical advantage from the industrial viewpoint.